Low-dose addition of silver nanoparticles stresses marine plankton communities. Issue 8 (3rd July 2018) - Tsiola, Anastasia; Toncelli, Claudio; Fodelianakis, Stilianos; Michoud, Grégoire; Bucheli, Thomas D.; Gavriilidou, Asimenia; Kagiorgi, Margarita; Kalantzi, Ioanna; Knauer, Katja; Kotoulas, Georgios; Mylona, Kyriaki; Papadopoulou, Eleftheria; et al.
Abstract : The release of silver nanoparticles (AgNPs) is expected to rise in the near future, with possible negative effects on aquatic life and enhancement of microbial resistance against AgNPs. Abstract : The release of silver nanoparticles (AgNPs) is expected to rise in the near future, with possible negative effects on aquatic life and enhancement of microbial resistance against AgNPs. However, a realistic evaluation of the toxicity of AgNPs to the marine ecosystem is currently missing. Therefore, we designed a mesocosm experiment to assess the impact of AgNP exposure on natural microbial plankton community dynamics in a coastal marine site at environmentally relevant concentrations. We monitored changes in the composition of the planktonic community, from viruses to protists. Further, we analyzed the concentration and properties of AgNPs for the total time of exposure. We found that the addition of AgNPs even at a low dose affected the plankton communities. Specifically, the growth of Synechococcus was inhibited and bacterial community composition significantly changed. Additionally, the amount of a lysogeny-related gene increased and viral auxiliary metabolic genes that are involved in cyanobacterial photosynthesis decreased, revealing a damaged photosynthetic potential after AgNP exposure. Microbial plankton was significantly affected due to both increased dissolved silver ions and decreased AgNP size. Our results highlight that the release of AgNPs alters the functioning of the marine food web by hampering important viral and bacterial processes.